2014
DOI: 10.1159/000367606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research in Surgery: Threats and Opportunities

Abstract: Surgery is a discipline which profoundly affects human integrity. Therefore, there is an ethical and scientific imperative that surgical practice depends on the best possible trial-based evidence. Traditionally, the quality and quantity of clinical research have been lagging behind other disciplines in clinical medicine. However, recent collaborative initiatives, such as the IDEAL framework which tests surgical innovation, international registries, and quality assurance platforms, the development of modified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…While research within the realm of surgery covers the full research spectrum from basic laboratory science through to clinical, population health and health services research, there has been a longstanding critical appraisal of the quality and quantity of surgical research . Rigorous research into the safety, effectiveness and cost effectiveness of therapeutic interventions underpins the development of evidence‐based practice standards and guidelines, yet surgery lags behind other medical disciplines in both the quantity and quality of its evidence base …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research within the realm of surgery covers the full research spectrum from basic laboratory science through to clinical, population health and health services research, there has been a longstanding critical appraisal of the quality and quantity of surgical research . Rigorous research into the safety, effectiveness and cost effectiveness of therapeutic interventions underpins the development of evidence‐based practice standards and guidelines, yet surgery lags behind other medical disciplines in both the quantity and quality of its evidence base …”
Section: Introductionmentioning
confidence: 99%
“…2 Rigorous research into the safety, effectiveness and cost effectiveness of therapeutic interventions underpins the development of evidence-based practice standards and guidelines, yet surgery lags behind other medical disciplines in both the quantity and quality of its evidence base. 3 Although randomized controlled trials (RCTs) are universally accepted as the optimal study design to test the effectiveness of clinical interventions, practical, ethical and methodological challenges often preclude their use in surgical effectiveness research. [4][5][6][7][8] An audit of the surgical literature found that only 3.4% of all articles in leading surgical journals were RCTs, 4 despite this study design being considered feasible for 40% of surgical effectiveness questions.…”
Section: Introductionmentioning
confidence: 99%
“…Not only new drugs, but also novel surgical interventions should be properly assessed. However, too stringent RCTs might not be the best format to achieve this [1,2] and might even stifle innovation. Therefore, we applaud that alternatives for the conventional RCT are being explored.…”
Section: Discussion: Toward a Learning Health Care System?mentioning
confidence: 99%
“…However, most surgeons feel that the format of this form of research suffers from various limitations including the felt lack of equipoise, and ethical problems related to the double-blinded design with sham surgery as a potential control. [1,2] Because of these limitations and the strict format of the RCT, surgeons have been reluctant to set up surgical trials, also because other trial formats may be more suitable. This is also defended or explained by “surgical exceptionalism,” the view that the somewhat exceptional ethical or regulatory status of surgery is justified by the unique nature of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These include time constraints, difficulties recruiting patients, utilization of particular research methodologies, limited research funding, a lack of collegiate support and research culture, few exemplars or mentors, low‐level requirements for research within surgical training and an absence of a defined training programme for surgical trainees seeking an academic pathway . Collectively, these challenges have resulted in a perceived lower academic standing and output for surgical research compared to other medical disciplines …”
mentioning
confidence: 99%